A Correlation of Alarin with Some Anthropometric Measurements in Iraqi Type II Diabetic Patients - Russell S. A. Al-Shaabani; Shakir F. T. Alaaraj (Medical Journal of Babylon)
Background: Diabetes mellitus (DM) is a group of chronic metabolic diseases that affect the body’s ability to produce insulin. It is one of the most common endocrine disorders. Objectives: This study aims to measure whether there was any association between alarin and some anthropometric measurements (AMs) such as waist/nick (W/N), waist/thoracic (W/T), waist/hip (W/H) in Iraqi type II diabetic patients. Materials and Methods: This study included 43 patients from Ramadi Teaching Hospitals, in addition to 43 healthy controls. Enzyme-linked immunosorbent assay was used to determine serum alarin level, while the fasting serum glucose (FSG) level was determined by enzymatic colorimetric methods. Results: Serum alarin (ng/mL) was higher in DM patients than in HCs (P < 0.0001), body mass index (BMI) was significantly higher in patients with T2DM, in addition, FSG) mg/dL (was higher in T2DM than HCs. Furthermore, alarin was positively associated with BMI (0.151), W/H (0.006), W/T (0.008), W/N (0.1260), and FSG (0.612). The receiver operating characteristic (ROC) curve indicates that alarin and FSG were excellent sensitive markers in the diagnosis of T2DM. Moreover, ROC indicated that W/N gave good sensitive signs. New values of the cutoff value for studied variables have been estimated as follows: alarin (>2.035 ng/mL), W/H (>0.9554), W/T (>0.9633), W/N (>2.665), H/T (>1.06), and FSG (>116.5 mg/dL). Conclusion: A very weak correlation appeared for alarin with AMs; the serum level of alarin was higher in T2DM than HCS; this means alarin may be used as a novel biomarker in the detection of T2DM and may be an effective biomarker in the diagnostic test for the disease.